Developmentally Sensitive Behavioral Treatment of a 4-Year-Old, Korean Girl With Selective Mutism. (October 2013) - Jacob, Marni L.; Suveg, Cynthia; Shaffer, Anne
This case study reports on the use of a developmentally sensitive behavioral treatment program for a 4-year-old Korean girl diagnosed with selective mutism. Multi-method assessment, consisting of parent and teacher reports, as well as school and home-video observation, confirmed the diagnosis. Behavioral therapy was administered with an emphasis on behavioral reinforcement strategies that were adapted for the child's developmental level. After 17 sessions, the child evidenced a notable reduction in selective mutism symptoms, evidenced by clinician and school observation. Furthermore, she indicated a decrease in symptoms of withdrawal based on teacher report. This case study demonstrates how behavioral treatment strategies emphasizing behavioral reinforcement techniques can be applied in developmentally appropriate ways to treat young, bilingual children with selective mutism.